Academic and professional publishing - Campbell, Robert 1946-; Pentz, Ed; Borthwick, Ian (Chandos Publishing series, 2012)
"Academic and professional publishing represents a diverse communications industry rooted in the scholarly ecosystem, peer review, and added value products and services. Publishers in this field play a critical and trusted role, registering, certifying, disseminating and preserving knowledge across scientific, technical and medical (STM), humanities and social science disciplines. Academic and Professional Publishing draws together expert publishing professionals, to provide comprehensive insight into the key developments in the industry and the innovative and multi-disciplinary approaches being applied to meet novel challenges. This book consists of 20 chapters covering what publishers do, how they work to add value and what the future may bring. Topics include: peer-review; the scholarly ecosystem; the digital revolution; publishing and communication strategies; business models and finances; editorial and production workflows; electronic publishing standards; citation and bibliometrics; user experience; sales, licensing and marketing; the evolving role of libraries; ethics and integrity; legal and copyright aspects; relationship management; the future of journal publishing; the impact of external forces; career development; and trust in academic and professional publishing. This book presents a comprehensive review of the integrated approach publishers take to support and improve communications within academic and professional publishing"--Publisher description.